Profitability and risk ratio of financial portfolio - I. Boháčková; L. Svatošová (Agricultural Economics (AGRICECON), 2002)
Financial portfolio represents a certain type of investments diversification and hence it issues a possibility how to reduce risk ratio and to ensure a sufficient profitability of financial investment. The paper shows ways of calculation and evaluation of investment possibilities. A base for the determination of the efficiency of portfolio particular parts is a rate of efficiency of particular securities and their weight (representation) in the portfolio. Risk of an investment action is linked to the results of the technical analysis of particular securities and of the mutual dependence among them, resp. of their mutual ability to influence each other. The contribution is worked out on a theoretical basis, nevertheless, the procedure can be applied easily to the investment possibility in the area of securities. It cannot be used in enterprises of agricultural primary production but it can be applied in the dimension of the agri-food complex, respectively in the agri-business dimension.